Observations on the growth of postlarvae of Macrohrachium rosenhergii in polythene sheet covered earthen nursery ponds during winter - Pillai, Bindu R; Tripathy, A P; Rao, K J (Indian Journal of Fisheries, 2011)
Growth of postlarvae of Macrohrachium rosenhergii reared in polythenecovered earthen nursery ponds (polyhouse) was evaluated during winter. Thepolyhouse ponds along with two control ponds (60 m^ each) were stocked withpostlarvae (0.013Â±0.004 g) at 40,000/ha stocking density. The prawns were fedwith a formulated feed (35 % crude protein) at the rate of 10 % of the biomassand were reared for 100 days. The percentage survival varied widely (24-82)in different ponds. Average daily growth in polyhouse nursery ponds was foundto be 83.72 % higher than the control ponds.